2014
DOI: 10.2478/s11686-014-0249-8
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic infections detected by FLOTAC in zoo mammals from Warsaw, Poland

Abstract: The aim of this study was to estimate the occurrence of intestinal parasites in groups of mammals kept in the Warsaw zoological garden (Poland). 71 pools of fecal samples were analyzed using the FLOTAC techniques. 48% of animals were positive and 47% of positivities showed multiple infections. Toxocara cati (71.4%) was found in felines; marsupials were infected with Coccidia (90%). Giardia spp. (24.0%), Blastocystis spp. (12.3%), Iodamoeba spp. (10.0%), Enterobius vermicularis (6.0%) and Entamoeba coli (3.3%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
4
19
0
1
Order By: Relevance
“…All of the gastrointestinal parasites identified in our study were described previously in zoo animals by other authors, and these parasites are known to be pathogenic to both animals and humans (animal handlers and zoo visitors) (FONTENOT et al, 2008;FAGIOLINI et al, 2010;TAHAS & DIAKOU, 2013;MAESANO et al, 2014;NOSAL et al, 2016;CRINGOLI et al, 2017). Gastrointestinal parasites of zoo mammals include zoonotic species and therefore their presence raises public health concerns, particularly Blastocystis spp.…”
Section: Discussionsupporting
confidence: 53%
“…All of the gastrointestinal parasites identified in our study were described previously in zoo animals by other authors, and these parasites are known to be pathogenic to both animals and humans (animal handlers and zoo visitors) (FONTENOT et al, 2008;FAGIOLINI et al, 2010;TAHAS & DIAKOU, 2013;MAESANO et al, 2014;NOSAL et al, 2016;CRINGOLI et al, 2017). Gastrointestinal parasites of zoo mammals include zoonotic species and therefore their presence raises public health concerns, particularly Blastocystis spp.…”
Section: Discussionsupporting
confidence: 53%
“…It has so far only been observed in Enhydra lutris and in turtles and fossil ichthyosaurs and plesiosaurs [ 64 , 65 ]. For this reason, homologous comparisons require a precisely cut transverse “perfect diaphyseal plane” (sensu [ 64 ]), i.e., the plane cutting the point where growth originated (see [ 65 ] for more details about this sectional plane). In order to locate such a cut, a longitudinal section of a rather long part of the central diaphysis is required.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to humans, Blastocystis spp. also exist in other mammals, such as dogs, cats, pigs, rats, and other primates . A recent study conducted in the Pacific northwest of the USA showed that carriage of Blastocystis was not associated with increased risk for gastrointestinal signs in shelter‐resident or client‐owned dogs and cats …”
Section: Classification Life Cycle and Pathogenicity Of Blastocystimentioning
confidence: 99%